Fungsi Strategi Pemasaran, Kualitas Layanan dan Kepercayaan Terhadap Loyalitas Nasabah - Susiana Mokhtar; Orfyanny Syahreffy Themba; Rezki Arianty Akob (Al-Buhuts, 2024)
This study aims to test the influence of marketing strategy on customer loyalty, test the influence of service quality on customer loyalty and the influence of trust on customer loyalty. The population in this study is all customers at PT Bank Sulselbar Makassar Head Office. The sampling technique is determined by purposive sampling, which is a technique for determining samples based on certain criteria. The criteria for selecting the sample taken in this study are customers at PT. Bank of South Sulawesi, Makassar. Malhotra 2006 if the population is large and the number is unknown, then the number of samples is calculated with 5-10 x Estimate Parameter. So the number of samples in this study is (5.20) = 100 people. In this study, the variables were measured using the Likert Scale. The data obtained were then processed using SPSS by means of multiple linear regression analysis. The results of the study found that marketing strategies have a positive and significant effect on customer loyalty, testing the influence of service quality has a positive and significant effect on customer loyalty and the influence of trust has a positive and significant effect on customer loyalty.